The dual-edged potential of AI autonomously defining loss functions - Abbas Ghori (Journal of Electrical Systems and Information Technology)
Abstract A loss function is one of the key components considered in machine learning as they steer the model toward the optimal performance by quantifying the discrepancy between the predicted outcome and the actual outcome. They predominantly act as guiding principles for any optimization algorithm, thereby influencing both the convergence characteristics as well as the generalization of the model. This paper discusses classical loss functions, including mean squared error (MSE), cross-entropy, Huber loss, and a range of other problem-specific variants that appear in scenarios dealing with imbalanced data, adversarial learning, and reinforcement learning. The advantages and limitations of these methods with respect to robustness, convergence speed, and computational efficiency are discussed. The applications are illustrated in crucial areas such as vision, NLP, and anomaly detection to reflect real-world relevance. The paper attempts to cover some of the upcoming trends in adaptive and meta-learned loss functions, emphasizing their prospects to ameliorate learning efficacy and interpretability of trained models. This review, integrating theoretical insight with practical implications, will help to better equip researchers and practitioners in choosing the appropriate loss function for their work, thereby serve the goal of developing more autonomous and efficient applications.